Sodium selenate biofortification, through seed priming, on dill microgreens grown in two different cultivation systems - Hossein Sheikhi; Silvana Nicola; Mojtaba Delshad; Roberta Bulgari (Frontiers in Plant Science)
Human health is significantly influenced by the quality of vegetables included in the diet. Soilless cultivation methods have the potential to enhance and standardize the levels of secondary metabolites or specific bioactive compounds in plants, even when utilizing LED lighting. In recent years, tailored foods, enriched with important microelements, are growing in popularity. The present research was conducted to explore the quantitative and qualitative aspects of dill (Anethum graveolens L.), grown either indoor or in a greenhouse and harvested during the microgreen stage. Seeds of dill were primed with 1.5 and 3 mg L−1 selenium (Se). Untreated dry and hydro-primed seeds were used as the control and positive control groups, respectively. Results demonstrated a higher yield in indoor farm environment (1255.6 g FW m−2) compared to greenhouse (655.1 g FW m−2), with a general positive effect on the morphological traits studied, with no significant influence from priming and Se. The mean value of phenolic index of microgreens grown in the greenhouse was 13.66% greater than that grown in indoor condition. It was also observed that seeds priming with Se can effectively raise the Se content in dill microgreens, in both tested conditions. Overall, our results suggest that the 3 mg L−1 Se seems to be the most promising concentration to obtain Se-enriched microgreens.